TREND KARTUN JEPANG TERHADAP PERILAKU BERKARYA KOMIK SISWA SMAN 1 PAINAN KABUPATEN PESISIR SELATAN - YUNI MELIA SARI, Yofita Sandra, S.Pd., M.Pd, Drs. Mediagus (Universitas Negeri Padang, 2015)
This research was intended to describe the trend of Japanese cartoon toward the students’ tendency in drawing comic at SMAN 1 Painan Kabupaten Pesisir Selatan. This research applied qualitative method and descriptive approach. The subject of the research was the students at SMAN 1 Painan Kabupaten Pesisir Selatan and Cultural Art teachers. The sources of the data were in the forms of written note, recording, photograph, video and the cartoon strips made by the students, and the students’ attendance list. The result of the research indicated that the students were more creative to make Japanese and Indonesian comic pictures. This could be seen from the characters of the cartoon which were in the form of strips. To draw comic strips, some students imitated pictures and some others did not. Then to draw pictures, the students did not copy the models, but when they did, they make them more exciting and funnier.Key Terms: The tendency of the students at SMAN 1 Painan in drawing comic